Legislative Changes in the Environmental Impact Assessment act in the Slovak Republic - Maslen, Michal (Public Governance, Administration and Finances Law Review, 2016)
The study is dealing with the implementation of the EIA Directive in the Slovak Republic, primarily focused on the participation of public in environmental proceedings. The case law presented a special approach on this field – partially which – leaded to new ways of interpretation of normative rules.